The Routledge handbook of EU copyright law - Rosati, Eleonora (Routledge handbooks, 2021)
The Routledge Handbook of EU Copyright Law provides a definitive survey of copyright harmonization in the European Union, capturing the essential and relevant issues of this relatively recent phenomenon. Over the past few years, two themes have emerged: on the one hand, copyright policy and legislative initiatives have intensified; on the other hand, the large number of references to the Court of Justice of the European Union has substantially shaped the EU copyright framework and, with it, the copyright framework of individual EU Member States. This handbook is a detailed reference source of original contributions which analyze and critically evaluate the state of EU copyright law with a view to detecting the key trends and patterns in the evolution of EU copyright, weighing the benefits and disadvantages of such evolution. It covers a broad range of topics through clusters focused on: the history and approaches to EU copyright harmonization; harmonization in the areas of exclusive rights, exceptions and limitations, and enforcement; copyright policy and legacy of harmonization. With contributions from a selection of highly regarded and leading scholars in this field, the Routledge Handbook on European Copyright Law is an essential resource for students and scholars who are interested in the field of copyright law.